2001
DOI: 10.1046/j.1369-6513.2001.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of patient information to support informed shared decision‐making

Abstract: Objectives (a) To ®nd out how much patient information material on display in family physicians' oces refers to management choices, and hence may be useful to support informed and shared decision-making (ISDM) by patients and (b) to evaluate the quality of print information materials exchanged during the consultation, i.e. brought in by patients or given out by family physicians.Design All print information available for patients and exchanged between physicians and patients was collected in a single complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 5 publications
0
35
0
2
Order By: Relevance
“…SDM principles seek to empower the individual (or parent) to make decisions, based on the provision of quality health information (Charles et al, 1997;Coulter & Ellins, 2007) and their own personal preferences (Godolphin et al, 2001). For SDM to be effective, sufficient time within consultations is required to allow for a full discussion of client preferences, concerns, and any other information relevant to the individual's health condition (Thistlethwaite, 2006).…”
Section: Shared Decision Making (Sdm) In the Context Of Asd Interventmentioning
confidence: 99%
See 3 more Smart Citations
“…SDM principles seek to empower the individual (or parent) to make decisions, based on the provision of quality health information (Charles et al, 1997;Coulter & Ellins, 2007) and their own personal preferences (Godolphin et al, 2001). For SDM to be effective, sufficient time within consultations is required to allow for a full discussion of client preferences, concerns, and any other information relevant to the individual's health condition (Thistlethwaite, 2006).…”
Section: Shared Decision Making (Sdm) In the Context Of Asd Interventmentioning
confidence: 99%
“…Some parents feel that they were given insufficient information from paediatricians at the time of their child's diagnosis (Osborne & Reed, 2008). With the limited time health practitioners have to spend with their clients (Kertoy, 2011;McMullan, 2005), they may not be able to adequately impart the information that is required for parents to make informed decisions (Godolphin, Towle, & McKendry, 2001, Hawk & Evans, 2013. Furthermore, some observations in the literature suggest that there are practitioners who avoid providing too much information for fear of overwhelming their clients with information .…”
Section: Shared Decision Making In the Context Of Autism Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly important given the potential disagreements between youth and their parents regarding treatment decisions. In a survey with 258 family medical students at the University of British Columbia, investigators found that conflict resolution and dealing with significant others, including parents, were two of the most challenging problems for SDM (Godolphin, Towle, & McKendry, 2001a, 2001b. Parents and youth may differ in their perceptions of involvement in the decision-making process.…”
Section: Practical Design Considerationsmentioning
confidence: 99%